Tracing nitrogen use efficiency of diverse Canadian spring wheat cultivars - Congreves, Kate A.; Otchere, Olivia; Hucl, Pierre J. (Frontiers in Plant Science, 2024)
Decades of wheat breeding have provided growers with numerous high-yielding options, but it is unknown if these yield improvements are likewise characterized with improved nitrogen use efficiency (NUE). Fertilizer nitrogen (N) is an ever-increasing expense, so improving NUE by reducing the requirement for N fertilizer without risking yield and quality is necessary. The goal of our research is to identify cultivars and associated traits that may improve NUE while maintaining productivity. We compared 25 spring wheat cultivars over a three-year period (2020, 2021, 2022) at two field sites differing in background soil N level for the ability to use fertilizer-N and allocate it to the grain. To do so, we employed the 15N stable isotope technique to trace the flow of fertilizer-N and determine the 15N recovery efficiency (15NRE). The 15NRE in the grain averaged 25.0% at the higher soil N site, and 15.5% at the lower soil N site. At the higher soil N site only, dwarfing alleles (Rht-B1b) were associated with greater 15NRE. Grain 15NRE was positively associated with yield, grain N content, and the 15N harvest index (15NHI) at the high soil N environment, but never at the low soil N environment. Our findings support the notion that the genetic development of high yielding semi-dwarf cultivars also translates into an improved ability to recover fertilizer-N—but this outcome is only expressed only under rich soil N conditions. Cultivars that simultaneously produced higher 15NRE and yields, grain N, or 15NHI differed by environment; possibly suggesting different mechanisms for improving crop NUE depending on background soil N level. Ultimately, cultivar-specific 15NRE information, including that presented here, will be useful breeders to design new crosses and approaches aimed at increasing NUE for spring wheat.